Waking the Buddha : how the most dynamic and empowering Buddhist movement in history is changing our concept of religion - Strand, Clark, 1957- (Santa Monica, CA : Middleway Press, 2014)
"Is there more to Buddhism than sitting in silent meditation? Is modern Buddhism relevant to the problems of daily life? Does it empower individuals to transform their lives? Or has Buddhism become too detached, so still and quiet that the Buddha has fallen asleep? Waking the Buddha tells the story of the Soka Gakkai International, the largest, most dynamic Buddhist movement in the world today--and one that is waking up and shaking up Buddhism so it can truly work in ordinary people's lives. Drawing on his long personal experience as a Buddhist teacher, journalist, and editor, Clark Strand offers broad insight into how and why the Soka Gakkai, with its commitment to social justice and its egalitarian approach, has become a role model, not only for other schools of Buddhism, but for other religions as well. Readers will be inspired by the struggles and triumphs of the Soka Gakkai's three founding presidents--individuals who staked their lives on the teachings of the Lotus Sutra and the extraordinary power of those teachings to help people become happy"--
"Is there more to Buddhism than sitting in silent meditation? Is modern Buddhism relevant to the problems of daily life? Does it empower individuals to transform their lives? Or has Buddhism become too detached, so still and quiet that the Buddha has fallen asleep? Waking the Buddha tells the story of the Soka Gakkai International, the largest, most dynamic Buddhist movement in the world today--and the one that has done more than any other to wake up and shake up Buddhism so it can once again work in ordinary people's lives. Drawing on his long personal experience as a Buddhist teacher, journalist and editor, Clark Strand offers broad insight into how and why the Soka Gakkai, with its commitment to social justice and its egalitarian approach, has become a role model, not only for other schools of Buddhism, but for other religions as well. Readers will be inspired by the struggles and triumphs of the Soka Gakkai's three founding presidents--individuals who staked their lives on the teachings of the Lotus Sutra...and on the extraordinary power of those teachings to help people become happy. These three men dared to revolutionize Buddhism by restoring it to its true purpose: to help people transform their lives and the world they live in. The result is a uniquely relevant form of Buddhism--one that "just makes sense" to the modern mind and is ready to meet the challenges of a global age. Waking the Buddha will appeal to anyone who wants something more out of Buddhism--or any religion-- as it explores the foundations of the Soka Gakkai's practical spiritual path in which people take the principles of Buddhism and put them to work in everyday life"--
Description based on print version record.
Keywords: Soka Gakkai International; Buddhism -- Social aspects; RELIGION / Buddhism / History; PHILOSOPHY / Buddhist; RELIGION / Comparative Religion; Electronic books